EDUKASI PEMBUATAN DAN PENGELOLAAN METODE PEMBAYARAN QRIS PADA PEDAGANG SATE BULAYAK DI DESA SURANADI KABUPATEN LOMBOK BARAT - I Gusti Agung Didit Eka Permadi; Asri Oktiani; Sri Ayu Febrianti; Sri Maryanti (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
QRIS (Quick Response Code Indonesian Standard) is one of the innovations introduced by Bank of Indonesia to facilitate system more payments efficient for perpetrator business and consumers. Sate Bulayak as a business culinary located in Suranadi Village, Narmada District, West Lombok Regency is one of the examples of MSMEs that are starting implementing QRIS as method payment for fulfil need increasingly consumers used to with digital transactions. The method used in activity devotion to public this is approach participatory with technique data collection and discussion in the form of observation direct, interviews, and studies documentation. Evaluation post implementation shows positive results. Sate Bulayak traders in Suranadi Village, Narmada District, West Lombok Regency experienced improvement in efficiency operational, because payment become faster and system recording transaction neater and easier monitored. Additionally, customers feel more comfortable because they no need again bring cash, enough with scan QRIS using application their digital wallet. Conclusions obtained that is in a way overall, activities devotion to public this has succeed give contribution big to development of MSMEs with introduce technology digital payments. Suggestions that can be recommended that is continuous mentoring is very important for Sate Bulayak traders can utilise technology this with better and safe from error in management digital payments.